Neoadjuvant Platinum-Based Chemotherapy is an Independent Predictor for Preoperative Thromboembolic Events in Bladder Cancer Patients Undergoing Radical Cystectomy - Browne, Cliodhna (Curr Urol, 2017)
INTRODUCTION: Neoadjuvant chemotherapy (NAC) confers a significant survival benefit in patients with muscle invasive bladder cancer. Platinum-based chemotherapy increases the risk of thromboembolic events (TEE). We determined the effect of cisplatin-based NAC on the incidence of preoperative TEEs in radical cystectomy patients. MATERIALS AND METHODS: A retrospective matched case-control study was performed on 55 patients undergoing radical cystectomy for muscle invasive bladder cancer. Group 1 (n = 20) included patients that received NAC prior to radical cystectomy and Group 2 (n = 35) included patients that underwent radical cystectomy without NAC. Logistic regression analyses tested potential predictors for TEEs in both groups (age, American Society of Anesthesiologists grade, use of NAC, histological subtype, pathological stage). RESULTS: In total, 6 patients of 55 developed a TEE. Five patients of 20 (25%) treated with NAC prior to radical cystectomy developed TEEs, while 1 of 35 (2.9%) treated with radical cystectomy alone developed a TEE. On univariate and multivariate regression analysis, NAC prior to radical cystectomy was an independent predictor for TEE prior to radical cystectomy (p = 0.033 and p = 0.043, respectively). The effect of perioperative anticoagulation on operative blood loss and postoperative hemoglobin level was not statistically significant between both groups (p = 0.22 and p = 0.08, respectively). CONCLUSION: Neoadjuvant cisplatin-based chemotherapy is a significant predictor for preoperative TEE in patients undergoing radical cystectomy.